The Influence of Public Infrastructure on Community Welfare in South Buru Regency - Sri Dewi Nurlette; Maryam Sangadji; Andre Sapthu (LP2M IAIN Palopo, 2026)
This study analyzes the influence of public infrastructure—particularly electricity and road infrastructure—on public welfare in South Buru Regency during the period 2010–2024. Using a quantitative time series approach and the Ordinary Least Squares (OLS) method, this study aims to measure the extent to which infrastructure improvements contribute to regional economic growth and improved public welfare. The variables used include electricity infrastructure (X1), road infrastructure (X2), and public welfare (Y), which is proxied by the level of economic growth and per capita income. The results of the analysis indicate that both electricity and road infrastructure have a positive and statistically significant influence on public welfare. This finding is in line with the public capital theory and endogenous growth theory, which state that infrastructure acts as a catalyst for economic activity and long-term welfare improvement. Therefore, it is recommended that the local government prioritize integrated infrastructure development policies between the energy and transportation sectors to encourage inclusive and sustainable economic growth in South Buru Regency